Covid 19: Access to Information and News In The Society - Andini Nurbahri; Zata Ismah; firmansyah (Prodi Manajemen Dakwah STAIN Mandailing Natal, 2022)
Information about Covid-19 spreads very quickly through social media as quickly as the virus spreads so that it can have both negative and positive impacts. The negative impact is panic, and the positive impact can be the government's partner in disseminating information related to Covid-19. This study aims to find out how the public's access to the news of covid-19. This research is quantitative with a cross sectional design. The research was conducted in 2022 in one of the women's study places in the Medan area. The number of samples was 40 people with an age range of 20 years to 80 years. The method of data collection is by interviewing the respondents. The results of the study showed that 1) Social media (instagram, facebook, youtube, twitter, tiktok) were the alternative media that most respondents chose to find initial information about Covid-19; 2) The majority of respondents access news about Covid-19 in one day (units of hour) with an average duration of < 1 hour; 3) The majority of respondents experienced changes in behavior due to mass media coverage related to Covid-19 in the form of adopting a healthy and hygienic lifestyle; 4) The majority of respondents stated that